2014
DOI: 10.3944/aott.2014.13.0049
|View full text |Cite
|
Sign up to set email alerts
|

Isolated foot metastasis of squamous cell carcinoma of the lung: a rare location

Abstract: Squamous cell carcinoma of the lung usually presents as a local rather than a metastatic disease. We present a 55-year-old male who was referred to the orthopedics and traumatology clinic for evaluation of pain and discomfort around the left ankle 2 months after diagnosis of locally advanced non-small cell (squamous cell) lung cancer. Physical examination revealed nonspecific pain and tenderness around the ankle. T2-weighted MR images showed lesions like a bone marrow edema around the talar head and neck. Whol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…The azo pigment red 210 used in our case is listed as “not to be used” in any kind of cosmetic agent . The tumor's anatomical location was unusual, with few cases of isolated metastasis of squamous cell carcinoma of the lung described in this region .…”
Section: Discussionmentioning
confidence: 99%
“…The azo pigment red 210 used in our case is listed as “not to be used” in any kind of cosmetic agent . The tumor's anatomical location was unusual, with few cases of isolated metastasis of squamous cell carcinoma of the lung described in this region .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated its utility in cases where traditional imaging, such as plain film or MRI, has been falsely negative, including patients with pigmented villonodular synovitis (PVNS) and metastatic lung cancer. 39,78…”
Section: Clinical Uses In Orthopedic Foot and Ankle Surgerymentioning
confidence: 99%
“…However, nuclear imaging modalities offer the ability to identify areas of pathology that may be occult on traditional imaging and, in the case of time-sensitive conditions, may provide diagnostic information days to weeks before other methods can. 39,82…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Das Azopigment Red 210, das bei unserer Patientin verwendet wurde, ist als ein Stoff aufgelistet, der in Kosmetika „keinesfalls verwendet werden darf“ . Die anatomische Lokalisierung des Tumors war ungewöhnlich, wobei einige wenige Fälle isolierter Metastasen von Plattenepithelkarzinomen der Lunge in diesem Bereich beobachtet worden sind .…”
Section: Diskussionunclassified